Primary pericardial angiosarcoma: case report and review of treatment options - Yadav, Udit (Ecancermedicalscience, 2020)
A primary cardiac angiosarcoma is a rare type of soft-tissue sarcoma with a high mortality rate. This report describes a young woman who presented with chest pain and worsening shortness of breath over the course of a year. She was diagnosed with and treated for latent tuberculosis and autoimmune pericarditis over the last year, however, her condition kept worsening. Further workup revealed a large pericardial and right atrial mass associated with multiple lung nodules. The biopsy from the lung mass showed angiosarcoma, and she was diagnosed with primary metastatic angiosarcoma of the pericardium. She was treated with doxorubicin and Ifosfamide (AIM-75 regimen), which led to a partial response. However, soon after completion of six cycles, the tumour progressed rapidly, leading to cardio-respiratory failure. In this report, we will discuss the clinical challenges and treatment options (surgical and medical) that are available for treating patients with angiosarcoma of the heart.